2021
DOI: 10.1007/s13132-021-00773-2
|View full text |Cite
|
Sign up to set email alerts
|

Financial Inclusion Measurement in the Least Developed Countries in Asia and Africa

Abstract: The purpose of this paper is to examine the determinants of financial inclusion in the least developed countries in Asia and Africa. We used World Bank data to estimate the probit econometric technique in the studied countries. The results show that young people and women are groups excluded from financial inclusion and that education and income are two of the key pillars for increasing financial inclusion. Furthermore, the results reveal that a higher level of financial inclusion increases the level of offici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 48 publications
0
21
1
Order By: Relevance
“…It brings an awareness of the use of advanced technology in the financial system. Due to the pandemic, apparent changes have occurred from all perspectives, and digital access to financial services is an urgent priority [ 54 ]. Substantial inequalities in developed and developing countries across vulnerable groups such as the poor, women, and the rural population still face low digital skills and financial incapability to own and use digital financial services [ 27 ].…”
Section: The Review Of Digital Financial Inclusionmentioning
confidence: 99%
“…It brings an awareness of the use of advanced technology in the financial system. Due to the pandemic, apparent changes have occurred from all perspectives, and digital access to financial services is an urgent priority [ 54 ]. Substantial inequalities in developed and developing countries across vulnerable groups such as the poor, women, and the rural population still face low digital skills and financial incapability to own and use digital financial services [ 27 ].…”
Section: The Review Of Digital Financial Inclusionmentioning
confidence: 99%
“…Both the studies posit similar results in that female heads are likely to opt for informal finance than institutional sources, as compared to male heads. Girón et al (2021) shared the same view in that the probability of a female possessing an official financial account is lesser than that of a male and women are likely to be dependent on informal financial sources. Doss et al (2019) also found more men acquiring financial assets through market in contrast to women.…”
Section: Resultsmentioning
confidence: 99%
“…The other study in Indian context (Malik et al, 2020) also found household income and expenditures to be significant determinants of credit demand in addition to education and employment. Gender difference along with other socio-economic factors such as access to education, ethnicity, income and lack of trust also hinders women's financial literacy and inclusion (Girón et al, 2021;Mishra et al, 2021). Mindra et al (2017) postulated that women's self-efficacy is a significant factor for women's financial inclusion.…”
Section: Findings From Studies At Household/individual Levelmentioning
confidence: 99%
“…Some writers posit that entrepreneurship is critical to the development and welfare of a society (e.g., O li, 2018;Méndez et al, 2012) and economy; however, they cannot thrive alone, as such, need support and enabling environment to thrive in, ranging from nance, judiciary, and general government policies (Dye and Alter, 2017). To this end, many scholars are yet to be satis ed with Nigeria's entrepreneurial engagement level if they talk about gaining economic stability (Girón et al, 2021;Nwoko et al, 2016;Eze and Ogiji, 2016). However, there are still discussions about entrepreneurship in Nigeria as there are more grounds to cover where the standpoint is and the direction to move.…”
Section: Theoretical Approachesmentioning
confidence: 99%